PERILAKU KONSUMEN DALAM PENGAMBILAN KEPUTUSAN STUDI DI JURUSAN MANAJEMEN UNIVERSITAS BUNDA MULIA, JAKARTA - Yenli Megawati (Universitas Bunda Mulia, 2017)
Universities need to analyze about consumer’s behaviour in doing studying decision because consumer are the buyers and who have the income to buy the products. There are some factors that affect consumer behaviour such as cultural factors, social factors, personal factors, and psychological factors. This research only search about social factores and personal factors, which one of the two factors really affect the decision about the major and university to study at Bunda Mulia University, Jakarta. This research used questionnaire as tools to gather the information needed and then the researcher analyze it by using SPSS ver 17.00. The conclusion of the research is that most of the consumer do the decision beacuse of personal factors and not because of social factorsKey words : consumer behaviour, persoanal, Social/Group Decision